Effects of the Chinese traditional fitness practice Wuqinxi on balance improvement in older women with a history of falls: a randomized controlled trial - Jiang, Yutao; Liu, Heng (Frontiers in Public Health, 2025)
ObjectiveThis study evaluated the impact of Wuqinxi Qigong, a traditional Chinese fitness practice, on the balance abilities of older women with a history of falls.MethodsParticipants in the experimental group (n = 35) and the control group (n = 36), matched for age, height, and weight, engaged in a 24-week Wuqinxi exercise program (three times per week, 70 min per session). Dynamic and static balance abilities were assessed at weeks 0, 12, and 24.ResultsWithin the experimental group, compared to baseline, the movement distance of the center of pressure with open eyes (left and right) decreased by 17.0 and 22.1% at weeks 12 and 24, respectively (p < 0.05). The movement distance with closed eyes, the total length of displacement of the center of pressure, and the speed of center of pressure (left and right) decreased by 17.1, 8.6, and 16.6% at week 24 (p < 0.05). The one-leg stand time with eyes open and closed increased by 47.7, 68.0, and 77.1%, 80.6% at weeks 12 and 24, respectively (p < 0.01). Compared to week 12, the one-leg stand time with eyes open increased by 19.9% at week 24 (p < 0.01).ConclusionA 24-week Wuqinxi exercise regimen enhances both static and dynamic balance abilities in older women with a history of falls. A longer regimen further improves static balance with eyes open compared to the 12-week mark.